Evaluation of extraction method on the structure and physicochemical properties of starch from seeds of two jackfruit varieties - Luciano, Carla Giovana; Landi Franco, Célia Maria [UNESP]; Ayala Valencia, Germán; do Amaral Sobral, Paulo José; Freitas Moraes, Izabel Cristina (Wiley, 2017)
Two main varieties of jackfruit (soft and hard) are commonly known in Brazil and contain a large amount of starch. This work aimed to evaluate the effect of extraction methods (aqueous and alkaline treatments) on the structural and physicochemical properties of starches from soft and hard jackfruit (Artocarpus heterophyllus) seeds. The jackfruit seed starch (JSS) granules were small (6.4–11.1 μm diameter), round, and bell-shaped with a smooth surface. Apparent amylose content ranged from 24 to 32% and was higher for the soft variety, which influenced several properties. The starches exhibited A-type XRD patterns, which contributed to the high peak gelatinization temperatures (72–81°C), and a crystallinity index ranging between 9.3 and 36.9%. Peak viscosities (2362–3373 cP) were similar to cassava starch. However, irrespective of the extraction method, the hard JSS had relatively higher pasting properties (peak viscosity and breakdown), swelling power, and solubility index (90°C) when compared to the soft JSS, which could be associated with the lower amylose content. Significant differences in lipid, protein, and amylose contents were observed in all starches extracted with the NaOH solution. The alkaline solvent decreased the average particle size of JSS by about 36%, probably causing a chemical gelatinization. Additionally, NaOH significantly reduced the crystallinity index and caused minor changes in granule morphology and swelling power.
Keywords: Alkali treatment; Jackfruit; Pasting properties; Structure; Thermal properties